Under the Spell of the Gauge Principle (Advanced Series in Mathematical Physics) - G. t Hooft (World Scientific, 1994)
This book features a collection of articles and review papers by the author on various subjects in quantum field theory, gauge field theory and quantum gravity. It covers: the mathematical aspects of the renormalization procedure needed to relate physically observable phenomena to the primary variables in these theories; a description of fundamental extended objects such as monopoles and instantons, aspects of quantum chromodynamics; and, finally, the author's approach to the problem of quantizing the gravitational force by considering black holes. All of these topics are important for the understanding of the elementary particles.